Rural-urban migration and subjective well-being the South African experience - Partridge, Andrew (School of Economics, 2014)
This paper gives a detailed account of rural-urban migration in South Africa. Using data from the recent National Income and Dynamics Study (NIDS) it defines the determinants and nature of rural-urban migration in South Africa before providing a thorough analysis of changes in a range of economic and social factors that individuals experience when they leave their rural homes and relocate to the country’s urban areas. These factors include income, housing standards, access to utilities, relative deprivation, interpersonal trust, crime and safety, physical health and depression. In particular the paper looks at subjective well-being, defined in terms of individuals self-reported satisfaction with life.